Understanding and evaluation of badminton shuttlecocks through flight dynamics and experimental approach - Lin, Calvin Shenghuai (2015)
Traditionally, a badminton shuttlecock is made with waterfowl feathers which are susceptible to supply inconsistency. This makes the synthetic shuttlecock an attractive alternative to the feather shuttlecocks. Despite good availability, the synthetic shuttlecocks remain unpopular because of criticism in performance. Current understanding of differences between feather shuttlecocks and the synthetic ones is limited. The lack of thorough testing method also means that the differences cannot be evaluated comprehensively. These impede the progress in shuttlecock development. The objective of this research is to develop a badminton shuttlecock testing framework for investigating and understanding the flight performance. The badminton shuttlecock was first investigated through numerical method that was validated with experimental results. Through study of cone models with openings (gaps) of various sizes, the high drag flight characteristic was explained through analysis of surface pressure and wake. The critical gap size–beyond which diminishes the blunt body effect and drag–shows that there is more than one design point for a performance target. The flight motion of a shuttlecock was explained by derivation of a system of equations. The axial spin, turnover and spin-induced yaw are three important flight behaviours that were modelled along with experimental data. The properties that should be identified for effective comparison of shuttlecocks were also identified from the model. Consequently, a three phase shuttlecock evaluation framework was developed. This system of tests aims to investigate the differences between the shuttlecocks while providing a reference value of good performance. In phase I, the static tests consisted of measurements of the physical properties and also wind tunnel experiment. Methods of measurement were developed and demonstrated. Misrepresentations in the usage of grain weight, characteristic area and drag coefficient as comparison tool were discussed. The wind tunnel experiment showed the tested synthetic shuttlecocks to have more drag per unit mass than the feather shuttlecocks. The one piece construction of the synthetic skirt also better resisted the skirt expansion at high flow-high spin conditions. The second phase of the testing framework consisted of flight testing where a unique experimental rig was developed. The experimental data and modelling showed the tested feather shuttlecocks having superior turnover performance. It also demonstrated the insufficiency of previous approaches in comparing turnover. The flight trajectories of 14 shuttlecock types were compared. Regardless of grade, the feather shuttlecocks had the same trajectory. However, the higher drag of the synthetics resulted in shorter flight range. Despite similar linear velocity profiles among the shuttlecocks, the axial spin rates differed. Analysing the spin rates and stall velocities showed the tested synthetic shuttlecocks and feather shuttlecocks to have the same post-stall trajectories. Finally, destructive testing was performed in Phase III to evaluate the durability of the shuttlecocks .A skirt compression machine, shuttlecock smash tester and feather vane wear machine were developed for testing. These original approaches to durability investigated the strength of the feather shaft and the degradation on the feather vane. Flight testing was subsequently conducted and the results differentiated the top tier feather shuttlecocks from the practise-grade ones. The major contribution of this research is the development of a comprehensive shuttlecock testing framework to provide knowledge on shuttlecock performance. It also offers an evaluation platform for future shuttlecock development.